Efektivitas Model Project Based Learning Berbantu Media Kubus Satuan Terhadap Hasil Belajar Matematika Siswa Kelas IV MI Miftahul Ulum Duriwetan - Irmayanti, Alfiyah; Nikmah, Khoirotun (Jurnal Murid, 2025)
This study aims to determine the effectiveness of the application of the Project Based Learning (PJBL) learning model assisted by unit cube media on the mathematics learning outcomes of grade IV students in cube materials. The research uses a quantitative approach with a pre-experimental design (one group pretest-posttest). The research subjects consisted of 14 students in grade IV of MI Miftahul Ulum Duriwetan. Data collection techniques use tests (pretest and posttest), observation, and documentation. The results of the analysis showed a significant increase in learning outcomes, with an average pretest score of 49.29 and a posttest of 84.71. The results of the paired sample t-test showed a significance value of 0.000 < 0.05, which means that there was a significant difference between the value before and after treatment. In conclusion, the PJBL model assisted by concrete media such as unit cubes is effective in improving students' understanding of mathematical concepts, especially in the material of building cube spaces